2005
DOI: 10.1002/bdra.20184
|View full text |Cite
|
Sign up to set email alerts
|

Nongenital malformations following exposure to progestational drugs: The last chapter of an erroneous allegation

Abstract: In the late 1960s and 1970s, a number of epidemiological studies were published indicating that pregnant women who were exposed to an array of sex steroids delivered infants with an increased incidence of nongenital congenital malformations. Because of these publications, the Food and Drug Administration (FDA), in conjunction with various pharmaceutical companies, labeled the therapeutic exposure of progestational drugs and contraceptives in pregnant women as a risk factor for limb-reduction defects (LRDs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 184 publications
0
17
0
1
Order By: Relevance
“…However, the evidence supporting the link between progestogens and contraceptive agents with nongenital malformations was contradictory, poor methodologically and the study material lacked uniformity [121,129,130]. By 1993 the controversy surrounding this issue meant that there had been 20 review articles written on this subject, none of which concluded that sex hormones produced nongenital organ teratogenesis [56,57].…”
Section: G03ab03/g03aa07mentioning
confidence: 99%
“…However, the evidence supporting the link between progestogens and contraceptive agents with nongenital malformations was contradictory, poor methodologically and the study material lacked uniformity [121,129,130]. By 1993 the controversy surrounding this issue meant that there had been 20 review articles written on this subject, none of which concluded that sex hormones produced nongenital organ teratogenesis [56,57].…”
Section: G03ab03/g03aa07mentioning
confidence: 99%
“…In 1999, the FDA revoked pregnancy warning labels for progestational agents (62), and they classified micronized progesterone, which is widely used in IVF treatments, as a category B drug. It appears that progesterone treatment does not increase the risk of nongenital birth defects.…”
Section: Progesteronementioning
confidence: 99%
“…Epidemiologic and animal studies have found no significant relationship between clinically administered progestational drugs and congenital malformations [33,34]. However, in one study, embryonic deaths occurred in pregnant rhesus monkeys treated with intramuscular injections of 17P [35].…”
Section: Currently Role Of Progeterone In Prematurity Preventionmentioning
confidence: 93%